THE EFFECT OF MOBILE PHONE USE ON MATHEMATICS PERFORMANCE IN ONLINE LEARNING AT ELEMENTARY SCHOOL - Windi Yuningsih; Roswita Lioba Nahak; Heryon Bernard Mbuik (Journal of Innovative Technologies in Learning and Education, 2024)
This study aimed to evaluate the effect of mobile phone use in online learning on mathematics performance among fifth-grade students at SD Inpres Sikumana II, Kupang. A quasi-experimental design was employed, involving 60 students divided into experimental and control groups. The experimental group used mobile phones intensively for accessing additional learning materials, video tutorials, and practice exercises, while the control group engaged in online learning with minimal mobile phone use. The results indicated a significant improvement in mathematics performance for the experimental group, with a mean post-test score of 75.6 compared to 65.3 for the control group. An independent t-test analysis revealed a statistically significant difference between the groups (t(58) = 4.89, p < 0.05), with a large effect size (Cohen’s d = 0.85). These findings suggest that mobile phones can be an effective tool for enhancing mathematics learning in an online environment, provided their use is properly managed and guided. However, the potential for distraction remains a concern, highlighting the need for teacher supervision to ensure mobile phones are used effectively for educational purposes. The study contributes to the existing literature on mobile learning and offers practical insights for educators and policymakers on integrating mobile technology into online learning strategies.